Dopamine receptor activation promotes adult neurogenesis in an acute Parkinson model - Winner, Beate; Hagl, Christian; Klucken, Jochen; Aigner, Ludwig; Masliah, Eliezer; Winkler, Jürgen; et al. (Experimental Neurology, 2009)
Cell proliferation of neural progenitors in the subventricular zone (SVZ) of Parkinson disease (PD) patients and animal models is decreased. It was previously demonstrated that the neurotransmitter dopamine modulates cell proliferation in the embryonic brain. The aim of the present study was to analyze whether oral treatment with the dopamine receptor agonist pramipexole (PPX) modulates adult neurogenesis in the SVZ/olfactory bulb system in a dopaminergic lesion model. 6-Hydroxydopamine (6-OHDA) lesioned adult rats received either PPX (1.0 mg/kg) or PBS orally twice daily and bromodeoxyuridine (BrdU, a cell proliferation marker) for 10 days and were perfused immediately after treatment or 4 weeks after PPX withdrawal. Stereological analysis revealed a significant augmentation in SVZ proliferation by PPX. Consecutively, enhanced neuronal differentiation and more new neurons were present in the olfactory bulb 4 weeks after PPX withdrawal. In addition, dopaminergic neurogenesis was increased in the olfactory bulb after PPX treatment. Motor activity as assessed by using an open field paradigm was permanently increased even after long term PPX withdrawal. In addition, we demonstrate that D2 and D3 receptors are present on adult rat SVZ-derived neural progenitors in vitro, and PPX specifically increased mRNA levels of epidermal growth factor receptor (EGF-R) and paired box gene 6 (Pax6).Oral PPX treatment selectively increases adult neurogenesis in the SVZ-olfactory bulb system by increasing proliferation and cell survival of newly generated neurons. Analyzing the neurogenic fate decisions mediated by D2/D3 signaling pathways may lead to new avenues to induce neural repair in the adult brain. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Adult neurogenesis; Neural progenitor cells; Dopamine; Parkinson; Dopamine agonist; Pramipexole